الاستشهاد بشعر أنور شاه الكشميرى في معارف السنن ليوسف بنورى: Poetic evidences of Anwar Shah al-Kashmiri in Ma’arif al-Sunan,explaining Sunan by Yusuf Bannuri - حافظ محمد سليم; دكتور حافظ محمد بادشاه (Al Manhal Research Journal, 2024)
Islam entered the subcontinent with Arab merchants, but scholars spread it everywhere, especially religious sciences and the Arabic language. The scholars contributed greatly to the spread of Islamic sciences and the Arabic language and their development. That is why I would like to introduce before you about the great scholar, hadith scholar, jurist and great scholar, Anwar Shah Kashmiri bin Muazzam Shah. He was born in Kashmir in the year 1875 AD and died in Deoband in the year 1933 AD. God willing, I will present in this short article a brief overview of his life,his scientific and literary services, his sheikhs, and his most famous students. The scholar Anwar Shah Al-Kashmiri had a great hand in all Islamic sciences and arts, especially in the Arabic language and literature, both in poetry and prose. Al-Banuri used to say about his sheikh that he did not like to read or read books except in the Arabic language, and for this reason he was skilled in Arabic literature.The original purpose of this brief article is that I will try to mention the method of quoting poetry and the types of poetic citation in Ma’arif al-Sunan, which was written by his student, Sayyid Yusuf Bannuri, Sharh al-Tirmidhi.It included the verses that Sayyid Yusuf al-Banuri used and transmitted in his book Ma’arif al-Sunan on the authority of his sheikh.In these verses, Sheikh Anwar Shah Kashmiri explained all the sections of the authentic hadith and the preference of the forbidden over the permissible with conclusive evidence and desirable reasons, and after that he came with the Persian verses, explaining there the terms related to the scale of weights and also the duties of the rituals of Hajj. There is no blood for leaving anyone with an excuse.